The role of Malaysian leaders in nation building process (1957-2003) - Shuib, Md. Shukri; Saludin, Mohamad Nasir; Feigenblatt, Otto F Von; Keling, Mohamad Faisol; Ajis, Mohd Na'eim (AstonJournals, 2010)
Generally,this paper discusses Malaysia's nation building process that includes the changing of national understanding from sultanate perspective towards democratic nation. In 1957, Malays achieved its independence. Ethnic Malays through United Malays National Organization (UMNO), ethnic Indian through Malaysian Indian Congress (MIC) are the major political parties, which at the time maintained separate identities, based on ethnicity. However,they had to compromise and unify for independence. This paper will also touch on the factors, which influence the process of nation building, especially internal and external factors. The role of several important leaders, especially former Prime Minister Mahathir Mohamed, Their policies and actions to develop and establish Malaysia's nation building process, is discussed.